1995
DOI: 10.1136/gut.36.4.564
|View full text |Cite
|
Sign up to set email alerts
|

Persistent measles virus infection of the intestine: confirmation by immunogold electron microscopy.

Abstract: This study sought to investigate persistent measles virus infection of the intestine: a novel protocol for immunogold electron microscopy was developed using a polyclonal anti-measles nucleoprotein antibody on reprocessed, formalin fixed paraffin wax embedded tissue sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 4 publications
0
32
0
1
Order By: Relevance
“…[44] Moreover, persistent measles infection has been detected in the intestinal tissue of 5 patients with CD by immunogold electron microscopy. [45] Epidemiological studies from Sweden would also suggest that there is an increased incidence of CD but not UC in people born during periods of documented measles epidemics. [46] These studies have raised the possibility that the neonate is more susceptible to either acute or persistent measles infection on account of its immature immune system.…”
Section: Environmental Factorsmentioning
confidence: 97%
“…[44] Moreover, persistent measles infection has been detected in the intestinal tissue of 5 patients with CD by immunogold electron microscopy. [45] Epidemiological studies from Sweden would also suggest that there is an increased incidence of CD but not UC in people born during periods of documented measles epidemics. [46] These studies have raised the possibility that the neonate is more susceptible to either acute or persistent measles infection on account of its immature immune system.…”
Section: Environmental Factorsmentioning
confidence: 97%
“…Although the list of studies is not inclusive, some investigators have shown an association, [39][40][41][42][43][44][45] while others reported no link between the measles vaccination and the development of inflammatory bowel disease. [46][47][48][49][50][51][52] It is important to note that 4 of the seven studies cited above as supporting an association have emanated from the Wakefield group.…”
Section: Scientific-association With Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…[46][47][48][49][50][51][52] It is important to note that 4 of the seven studies cited above as supporting an association have emanated from the Wakefield group. 39,41,42,44 At this time, epidemiological and pathological studies by different investigators have provided conflicting results. For this reason, many organization have concluded that a link cannot be established.…”
Section: Scientific-association With Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Plus réce-ment, l'hypothèse d'une infection par le virus de la rougeole dans la maladie de Crohn a été avancée. Deux observations sont en accord avec cette hypothèse : la présence du virus morbilleux dans les lésions intestinales [8] et l'augmentation du risque de développer une maladie de Crohn chez les sujets vaccinés contre la rougeole [9]. Enfin, le rôle d'antigènes intraluminaux non spécifiques de la flore résidente de l'intestin a été évoqué devant l'influence du flux fécal dans le déclenchement des poussées de la maladie.…”
Section: La Composante Génétique Des Maladies Inflammatoires Du Tube unclassified